The dark side of private life of women in Lodz – a contribution to the problem of murdering children by women in „Goniec Łódzki” - Czekalska, Adrianna (Marginesy, 2021)
Infanticide – as a form of profit – was and is the darkest side of the private life of people who lived in factory towns. The case of women who killed children for profit is shocking, because they did it in their own homes, living a perfectly normal private life every day and watching the slow agony of the children they were starving. The analysis of „Goniec Łódzki” shows how dramatic was the private life of the poorest part of society, which lived in industrial towns of Russian Empire. The aim of this article is not to thoroughly analyze the reasons of infanticide, but shows the dramas that took place behind closed doors in Lodz at the turn of the 19th and 20th centuries.